2018
DOI: 10.1053/j.gastro.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

GS-0976 Reduces Hepatic Steatosis and Fibrosis Markers in Patients With Nonalcoholic Fatty Liver Disease

Abstract: In a randomized placebo-controlled trial of patients with NASH, we found 12-week administration of GS-0976 20 mg decreased hepatic steatosis, selected markers of fibrosis, and liver biochemistry. ClinicalTrials.gov ID NCT02856555.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
246
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 277 publications
(262 citation statements)
references
References 38 publications
12
246
1
3
Order By: Relevance
“…This increase was independent of changes in plasma insulin concentrations and likely reflects increases in hepatic acetyl‐CoA content, which has been shown to increase hepatic gluconeogenesis through allosteric activation of pyruvate carboxylase . The opposing effects of increased hepatic insulin sensitivity and increased HGP may explain the lack of an effect on fasting plasma glucose observed in this study and in patients with NASH treated for 12 weeks with GS‐0976 . The net effect of these changes on long‐term glycemic control in patients with metabolic dysfunction requires further clinical investigation.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…This increase was independent of changes in plasma insulin concentrations and likely reflects increases in hepatic acetyl‐CoA content, which has been shown to increase hepatic gluconeogenesis through allosteric activation of pyruvate carboxylase . The opposing effects of increased hepatic insulin sensitivity and increased HGP may explain the lack of an effect on fasting plasma glucose observed in this study and in patients with NASH treated for 12 weeks with GS‐0976 . The net effect of these changes on long‐term glycemic control in patients with metabolic dysfunction requires further clinical investigation.…”
Section: Discussionmentioning
confidence: 66%
“…Multiple studies support pharmacologic inhibition of ACC1 and ACC2 for the treatment of NAFLD through simultaneous inhibition of DNL and stimulation of fatty acid oxidation . In particular, two clinical trials of the liver‐directed ACC inhibitor GS‐0976 found statistically significant decreases in hepatic steatosis and the marker of fibrosis tissue inhibitor of metalloproteinase 1 in patients with NASH and fibrosis . However, the effect of ACC inhibition on hepatic mitochondrial oxidation, gluconeogenesis, hepatic glucose production, and ketogenesis in vivo has not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACC inhibitors decrease hepatic triglyceride contents, which is attributable to anticipated effects of reducing de novo lipogenesis and increasing rates of fatty acid oxidation. These findings have now been validated in a phase II trial of a liver‐targeted, allosteric inhibitor of ACC1 and ACC2, which demonstrated reduced hepatic steatosis and improved markers of fibrosis …”
mentioning
confidence: 83%